Analisis Perlakuan Pajak Penghasilan Pasal 23 Atas Jasa untuk Menetapkan Fee Fintech Peer to Peer Lending PT Esta Kapital Fintek pada PT Esta Dana Ventura - Sri Mulyani; Adi Rizfal Efriadi (Jurnal Manajemen, 2021)
The purpose of this study is to analiyze how to calculations determination of Fintech Peer to Peer Lending fees conducted by PT Esta Dana Ventura from coorporation with PT Esta Kapital Fintek as well as what treatment income tax article 23 on this fee is in accordance with the law applicable taxation. The research design used in this study is to use qualitative methode. Income tax treatment article 23 on Fintech Peer to Peer Lending services starting from recording and the deducation is in accordance with the applicable tax regulation, namly Law No. 36 of 2010. This can be seen from the amount of taxes which was deducated for the Peer to Peer Lending services of PT Esta Dana Ventura equal from the amount of tax withheld by the tax office. The size taxes that must be paid by PT Esta Dana Ventura in 2019 for Fintech services is Rp. 57.875.506.